1997
DOI: 10.1007/bf02407461
|View full text |Cite
|
Sign up to set email alerts
|

Mercury pollution from small gold mines in China

Abstract: Abstract. Small scale gold mining activity in some mountainous areas of China has caused a series of Hg pollution problems. Preliminary study indicated that impacts of rig pollution on the surrounding environment, air, water and soil are dramatic, and human contamination requires attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Airborne Hg concentrations inside workshops of a small scale gold amalgamation mining facility ranged from 2.0 to 2.8 mg m − 3 close to Hg 0 vapour saturation (Lin et al, 1997), which significantly exceeds the upper limit (0.01 mg m − 3 ) for occupational exposure by China's national standard. TGM concentrations in ambient air of the Tongguan gold mining area were significantly elevated compared to the regional background, with a maximum of 18 μg m − 3 observed at a gold mill ) in the crops sampled in this study ).…”
Section: Other Hotspot Areasmentioning
confidence: 99%
See 3 more Smart Citations
“…Airborne Hg concentrations inside workshops of a small scale gold amalgamation mining facility ranged from 2.0 to 2.8 mg m − 3 close to Hg 0 vapour saturation (Lin et al, 1997), which significantly exceeds the upper limit (0.01 mg m − 3 ) for occupational exposure by China's national standard. TGM concentrations in ambient air of the Tongguan gold mining area were significantly elevated compared to the regional background, with a maximum of 18 μg m − 3 observed at a gold mill ) in the crops sampled in this study ).…”
Section: Other Hotspot Areasmentioning
confidence: 99%
“…The study of Lin et al (1997) indicated serious environmental Hg pollution in the gold producing area, where total-Hg concentrations in solid tailings and soils near the workshops were highly elevated (up to 100-300 mg kg − 1 and 1100 mg kg − 1 , respectively). Soil samples collected in the vicinity of gold mills in the Tongguan gold mining area were also significantly contaminated (concentration range of total-Hg: 0.9 to 76 mg kg − 1 ) .…”
Section: Other Hotspot Areasmentioning
confidence: 99%
See 2 more Smart Citations
“…Mercury (Hg) is a globally toxic pollutant and has been of wide public health concern during the past decades (Feng and Qiu 2008;Hammond 1971;Lin et al 1997;Lin et al 2012;. Anthropogenic emissions are considered to be the main source of global Hg contamination and have been estimated to account for 2320 t annually (Pirrone et al 2010).…”
Section: Introductionmentioning
confidence: 99%